Efeito do guaraná (Paullinia cupana) no metabolismo de nucleotídeos e nucleosídeo de adenina em um modelo experimental de hipercolesterolemia - Ruchel, Jader Betsch (2013)
Hypercholesterolemia is a metabolic disease characterized by high levels of serum low density lipoproteins and total cholesterol, associated with the inflammatory disorders, the migration of monocytes and T cells and with an endothelial dysfunction. The purinergic signaling system plays an important role in the modulation of inflammatory and immune response by extracellular biomolecules such as adenine nucleotides and their derived nucleoside adenosine, which are essential for the initiation and maintenance of response inflammatory. The effects of these molecules are promoted by the action of purinergic receptors specifics and controlled by ectoenzymes, in cell surface. Based on these principles, this study investigated the effect of guaraná on the activity of the E-NTPDase and E-ADA in lymphocytes, as well as analyze the biochemical parameters in rats with induced hypercholesterolemia by diet. The rats were divided in eight groups, of which four were induced hypercholesterolemia and the other four groups received normal diet. The animals in each diet were subdivided according treatment, saline, guaraná 12.5, 25 and 50 mg/kg/day orally for 30 days. There was observed an increase in 74% in ATP hydrolysis by E-NTPDase activity in lymphocytes of rats with hypercholesterolemia treated at doses of 25 and 50 mg/kg/day when compared with all other groups. However, E-NTPDase activity was not altered when used ADP as substrate for these three doses. Moreover, the hypercholesterolemic group treated with the higher concentration showed higher decreased of about 70% in E-ADA activity than the other normal diet groups. Was also observed that the guaraná was able to reduce to basal levels, total cholesterol and LDL-C in hypercholesterolemic rats. In addition, the guaraná in high concentrations when associated with hypercholesterolemic diet was able to increase the ATP hydrolysis and decrease the E-ADA activity in lymphocytes, contributing to reducing the inflammatory process. Although requiring further study, guaraná could be used as a complementary therapy for the benefit of people with hypercholesterolemia.